Lung immunoglobulin A immunity dysregulation in cystic fibrosis - Amandine M. Collin (EBioMedicine, 2020)
Background: In cystic fibrosis (CF), recurrent infections suggest impaired mucosal immunity but whether production of secretory immunoglobulin A (S-IgA) is impaired remains elusive. S-IgA is generated following polymeric immunoglobulin receptor (pIgR)-mediated transepithelial transport of dimeric (d-)IgA and represents a major defence through neutralisation of inhaled pathogens like Pseudomonas aeruginosa (Pa). Methods: Human lung tissue (n = 74), human sputum (n = 118), primary human bronchial epithelial cells (HBEC) (cultured in air-liquid interface) (n = 19) and mouse lung tissue and bronchoalveolar lavage were studied for pIgR expression, IgA secretion and regulation. Findings: Increased epithelial pIgR immunostaining was observed in CF lung explants, associated with more IgA-producing plasma cells, sputum and serum IgA, especially Pa-specific IgA. In contrast, pIgR and IgA transport were downregulated in F508del mice, CFTR-inhibited HBEC, and CF HBEC. Moreover, the unfolded protein response (UPR) due to F508del mutation, inhibited IgA transport in Calu-3 cells. Conversely, pIgR expression and IgA secretion were strongly upregulated following Pa lung infection in control and F508del mice, through an inflammatory host response involving interleukin-17. Interpretation: A complex regulation of IgA secretion occurs in the CF lung, UPR induced by CFTR mutation/dysfunction inhibiting d-IgA transcytosis, and Pa infection unexpectedly unleashing this secretory defence mechanism. Funding: This work was supported by the Forton's grant of the King Baudouin's Foundation, Belgium, the Fondazione Ricerca Fibrosi Cistica, Italy, and the Fonds National de la Recherche Scientifique, Belgium.